Adrenal activity and renal function in the four-striped field mouse, Rhabdomys pumilio (Sparrman), with special reference to differences between the sexes - Mouton, Pieter leFras Nortier (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- Univ. of Stellenbosch, 1980.